Perancangan Campuran Self Compacted Concrete Berdasarkan Kuat Tekan dan Aliran Mortar Maksimum Menggunakan Agregat Kering Udara - Morib, Margeritha Agustina; Zai, Hironimus Firnius; Ariyani, Ninik (Universitas Kristen Maranatha, 2024)
The use of Self Compacted Concrete (SCC) in construction industry continues to grow. Different levels of work complexity require varying flow rates and SCC compaction capabilities. Mix design for SCC cannot be defined precisely because there are many parameters involved. This study used a stepwise design method by determining maximum fly ash composition for type I cement substitution which produced highest mortar compressive strength. Superplasticizer added to produce flow mortar more than 250 mm. Air-dried Progo Sand (Gradation IV) and air-dried Clereng Gravel size 4.8 mm – 9.6 mm was used. SCC was obtained by adding gravel into mortar using coefficient of 1.4; 1.6 and 1.8 from 1 m3 volume of agregat cavity. Fresh concrete rheological tests include slump flow, v-funnel, L-box and segregation resistance to determine SCC class. The compression test of 3 cubes mortar for each variation was carried out at 3 days while 3 cylinder SCC compression test for each variation was carried out at 3 and 28 days. Cement substitution with 10% fly ash and 1.8% superplasticizer gave flow mortar of 320.65 mm and compressive strength of 22.07 Mpa was chosen as the SCC mortar. SCC using coefficient of 1.8 produces compressive strength of 30.48 MPa.